KESADARAN HUKUM MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA BONEDAA KECAMATAN SUWAWA SELATAN KABUPATEN BONE BOLANGO - Lucyane Djaafar; Nopiana Mozin (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
The low and not yet optimal legal awareness of the community in paying land and building taxes is one of the problems faced in Indonesia, as well as in Bonedaa Village, South Suwawa District, Bone Bolang Regency. Not optimal and low public knowledge about legal awareness in paying taxes, can result in development not going well and smoothly, the government is also not sufficient to meet regional needs, regional foreign exchange is reduced so that it can lead to a buildup of debt. This study aims to determine how the public's legal awareness in paying land and building taxes. The research method uses the methodqualitative, namely in the form of data collection through library research and field data. Based on the results of the study, it shows that the lack of legal awareness of the people of Bonedaa Village, South Suwawa District, Bone Bolango Regency in paying land and building taxes is caused by several factors, namely the economy, lack of socialization and lack of public awareness in paying taxes on time. To increase public legal awareness in paying taxes, the government must provide an understanding of the importance of paying taxes, either through socialization, through print or electronic media, so that people can understand the tax.